A randomized crash injury prevention trial of transitioning high-risk elders from driving. Issue 1 (July 2015) - Stowe, James D.; Cooney, Teresa M.; Bonne, Stephanie; Meuser, Thomas M.; Berg-Weger, Marla; Schmidt, Nicholas; Coughenour, Jeffrey
<x xml:space="preserve">Abstract</x> Supplemental digital content is available in the text. BACKGROUND Older adults with medical conditions that impair function are at risk for experiencing a motor vehicle crash. This randomized controlled trial tested an intervention to reduce crash-related risk among older patients. METHODS A 2-to-1 allocation ratio resulted in comparisons between 26 intervention and 13 attention control (n = 39) group members who were recruited from inpatient and outpatient settings. The intervention consisted of two sessions of facilitated planning in which participants' health, transportation alternatives, attitudes/emotions regarding a change in mobility, and actions to ensure continued safe mobility were discussed. Moreover, all participants received supportive telephone calls during the 6-month intervention period. RESULTS Results showed that when compared with the control group, the intervention group had significantly better subjective health, had fewer high-risk driving behaviors, and drove less distance on excursions from home at follow-up. Yet, simple repeated-measures analyses were not significant. CONCLUSION Results suggest that facilitated planning may help ease the transition to driving retirement among some high-risk older patients. Larger samples and longer study duration are needed to confirm these effects and to measure direct crash and injury outcomes. A significant proportion of high-risk patients do not plan for driving retirement and remain a crash risk. LEVEL OF EVIDENCE Therapeutic/care management study, level III.